2015
DOI: 10.3923/jm.2015.343.354
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Hazard of Zoonotic Campylobacter jejuni Reference to Egyptian Regional and Seasonal Variations

Abstract: Several Campylobacter species are known to be pathogenic to humans, with Campylobacter jejuni being the main leading cause of campylobacteriosis worldwide. The present investigation aimed to detect C. jejuni from chicken, water, milk and milk products and humans among 4 Egyptian Governorates (Cairo, Fayoum, Minya and Qalubiya) using conventional method and PCR 146 C. jejuni isolates with an incidence of 6.2% were confirmed to species level by polymerase chain reaction through detection of MapA gene. high incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…Yersinia enterocolitica was found in homemade yogurt (made from pasteurized milk) that was involved in an outbreak in Pennsylvania in 2011 (Centers for Disease Control and Prevention, 2011). Omara et al (2015) analyzed yogurt samples in Egypt for the presence of Campylobacter jejuni and found 4.4% to be positive by isolation and biochemical identification and 1.2% to be positive by PCR detection of the MapA gene. Amer et al (2010) found that enterohemorrhagic Escherichia coli and Yersinia enterocolitica were no longer present during storage for 10 and 4 d, respectively.…”
Section: Keeping Quality and Safety Of Yogurtmentioning
confidence: 99%
“…Yersinia enterocolitica was found in homemade yogurt (made from pasteurized milk) that was involved in an outbreak in Pennsylvania in 2011 (Centers for Disease Control and Prevention, 2011). Omara et al (2015) analyzed yogurt samples in Egypt for the presence of Campylobacter jejuni and found 4.4% to be positive by isolation and biochemical identification and 1.2% to be positive by PCR detection of the MapA gene. Amer et al (2010) found that enterohemorrhagic Escherichia coli and Yersinia enterocolitica were no longer present during storage for 10 and 4 d, respectively.…”
Section: Keeping Quality and Safety Of Yogurtmentioning
confidence: 99%
“…In the period from 2006 to 2015, several studies described the isolation of Campylobacter , mainly C. jejuni , in chickens, raw milk, milk products, diarrheic and normal camel calves and stool of diarrheic patients in several governorates in Egypt [ 19 , 20 , 21 , 22 , 23 ]. Backyard poultry remains the main source of Campylobacter transmission to humans [ 24 , 25 , 26 ]. In one governorate, Campylobacter spp.…”
Section: Bacterial Zoonosismentioning
confidence: 99%
“…This incidence was in close agreement with that (12.82%) detected by Abd El-Tawab et al (2015) from chicken breast meat. Lower rates (10%) were revealed by Chatur (2014) and in Egypt (9.6% &10%) by Omara et al (2015) and Hafez et al (2018) respectively. However, higher prevalence (46.9%, 16.6% &18.33%) were found by Wieczorek et al (2012), Elgabry et al (2016) and Modirrousta et al (2016) respectively.…”
Section: Discussionmentioning
confidence: 85%
“…This prevalence could be due to the intestinal tract of chickens, especially the caecum and colon, which is considered an area of tropism for a large number of Campylobacter species (Jokinen et al, 2011). Lower rates of contamination were detected in Egypt in previous studies Omara et al (2015), Youseef et al (2017), Elsayed et al (2019), with C. jejuni isolation rates of 12.8%, 4% and 14.7%, respectively. However, higher rates of isolation (33.3%, 72.1%) were revealed by Abd El-Tawab et al 2018 In our study, C. jejuni isolates (16.66%) were derived from liver samples because the liver is considered an organ of tropism for C. jejuni (Boukraa et al, 1991).…”
Section: Discussionmentioning
confidence: 87%